Methods of Election Manipulation and the Likelihood of Post-Election Protest. Issue 4 (12th October 2020) - Harvey, Cole J.; Mukherjee, Paula
Abstract: The risk of popular protest is one of the few deterrents against election manipulation in authoritarian regimes and unconsolidated democracies, but why are some fraudulent elections met with popular protest while others are not? We use data from elections in 108 countries, from 1980 to 2004, to show that the regime's choice of election manipulation tactics affects the likelihood of post-election protest. Leaders signal their strength and resources by manipulating elections, but some manipulation tactics send stronger signals than others. We find that opposition groups are more likely to protest when relatively cheap administrative fraud is employed, but not when more costly forms of manipulation – extra-legal mobilization and voter intimidation – are used. This study demonstrates the importance of accounting for variation in electoral manipulation tactics, and the information communicated by those tactics, in explaining post-election protest and the stability of electoral authoritarian and newly democratic regimes.